History of leprosy in Rio de Janeiro - João Carlos Regazzi Avelleira; Fred Bernardes Filho; Maria Victória Quaresma; Francisco Reis Vianna (Anais Brasileiros de Dermatologia, 2014)
The record of the first cases of leprosy in Rio de Janeiro dates from the seventeenth century. The first local host of leprosy patients was created from 1741, and the first colonies hospitals were built in the early twentieth century, in order to avoid contagion of the population. The first structures dedicated to research also date from this time: the Leprosy International Institute, the Leprology Institute, and the Leprosy Laboratory of the Oswaldo Cruz Foundation, where the most prestigious leprologists of Rio de Janeiro worked. Currently, investigations are focused on the Oswaldo Cruz Foundation; additionally, leprosy patients are treated at municipal health centers and state hospitals, and former colony hospitals only accept patients with severe disabilities.